PROJECT OF EDUCATIONAL PLATFORM, WHICH USES SEMANTIC WEB ADVANTAGES - Glibovets, M.M.; Gorokhovskiy, C.C.; Lavrovich, T.O. (Journal of Information Technologies in Education (ITE), 2010)
In this work the prospects of the use of Semantic Web technology in an electronic learning process are examined. General description of technology, its constituents are given, the necessities of modern studies are analyzed and the influence of Semantic Web is explained in this sphere.